The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/1476-511x-13-199
|View full text |Cite
|
Sign up to set email alerts
|

Palmitoleic acid (n-7) increases white adipocytes GLUT4 content and glucose uptake in association with AMPK activation

Abstract: BackgroundPalmitoleic acid was previously shown to improve glucose homeostasis by reducing hepatic glucose production and by enhancing insulin-stimulated glucose uptake in skeletal muscle. Herein we tested the hypothesis that palmitoleic acid positively modulates glucose uptake and metabolism in adipocytes.MethodsFor this, both differentiated 3 T3-L1 cells treated with either palmitoleic acid (16:1n7, 200 μM) or palmitic acid (16:0, 200 μM) for 24 h and primary adipocytes from mice treated with 16:1n7 (300 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 44 publications
6
71
1
1
Order By: Relevance
“…For example, Yang et al [49] showed that palmitoleic acid induces satiety in mice, while studies with obese high-fat diet fed mice have shown that daily administration of palmitoleic acid (300 mg kg −1 ) for 10 d increased whole body insulin sensitivity [4,51] and enhanced glucose uptake into adipose tissue by modulation of GLUT-4 content and AMPK phosphorylation. [5] Palmitoleic acid also increased expression of adipose triglyceride lipase and hormone-sensitive lipase (HSL) [24] (Figure 2). This higher expression and activity of Figure 1) reportedly increases insulin secretion by the pancreas, improves insulin sensitivity of the liver and skeletal muscle, reduces inflammation, and promotes numerous beneficial metabolic effects in the liver and cardiovascular system.…”
Section: Obesity and Dyslipidemiamentioning
confidence: 97%
See 3 more Smart Citations
“…For example, Yang et al [49] showed that palmitoleic acid induces satiety in mice, while studies with obese high-fat diet fed mice have shown that daily administration of palmitoleic acid (300 mg kg −1 ) for 10 d increased whole body insulin sensitivity [4,51] and enhanced glucose uptake into adipose tissue by modulation of GLUT-4 content and AMPK phosphorylation. [5] Palmitoleic acid also increased expression of adipose triglyceride lipase and hormone-sensitive lipase (HSL) [24] (Figure 2). This higher expression and activity of Figure 1) reportedly increases insulin secretion by the pancreas, improves insulin sensitivity of the liver and skeletal muscle, reduces inflammation, and promotes numerous beneficial metabolic effects in the liver and cardiovascular system.…”
Section: Obesity and Dyslipidemiamentioning
confidence: 97%
“…[26] It is important to mention that besides being rich in palmitoleic acid (19%), macadamia oil has a high percentage of oleic acid (56%). [26] However, most of the animal studies presented here [4,5,24,51] compared the treatment of palmitoleic acid to that of oleic acid (e.g., at 300 mg kg −1 ), showing a higher oxidative, lipid lowering, and insulin sensitization with palmitoleic acid.…”
Section: Obesity and Dyslipidemiamentioning
confidence: 99%
See 2 more Smart Citations
“…7) Subsequent studies performed on cultured cells, animals, and humans have suggested that 16:1n-7 enhances whole-body glucose disposal, suppresses hepatic steatosis, reduces stearoyl-CoA desaturase (SCD) 1, and modulates the metabolism of triacylglycerols (TAG) and glucose in white adipose tissue. [6][7][8][9] These findings generated expectations on the physiological significance of 16:1n-7 for metabolic homeostasis in humans. However, several lines of evidence from studies performed on human subjects have suggested contradictory outcomes; namely, circulating levels of 16:1n-7 are not necessarily beneficial for human health.…”
mentioning
confidence: 99%